2015
DOI: 10.3390/e17106872
|View full text |Cite
|
Sign up to set email alerts
|

Topological Characterization of Complex Systems: Using Persistent Entropy

Abstract: In this paper, we propose a methodology for deriving a model of a complex system by exploiting the information extracted from topological data analysis. Central to our approach is the S[B] paradigm in which a complex system is represented by a two-level model. One level, the structural S one, is derived using the newly-introduced quantitative concept of persistent entropy, and it is described by a persistent entropy automaton. The other level, the behavioral B one, is characterized by a network of interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…By offering high spatial resolution combined with long time scales as well as the unique set of capabilities, for example particle tracking and stochasticity, ABM provides a platform for molecular systems biology that could not be achieved through any other single computational method. In addition, integration of ABM with data‐driven methods, for example topological data analysis (TDA), provides further capabilities in analysis of complex molecular systems . While several studies have already demonstrated the utility of ABM in molecular systems biology, ABM is not yet commonly employed in biological simulations.…”
Section: Discussionmentioning
confidence: 99%
“…By offering high spatial resolution combined with long time scales as well as the unique set of capabilities, for example particle tracking and stochasticity, ABM provides a platform for molecular systems biology that could not be achieved through any other single computational method. In addition, integration of ABM with data‐driven methods, for example topological data analysis (TDA), provides further capabilities in analysis of complex molecular systems . While several studies have already demonstrated the utility of ABM in molecular systems biology, ABM is not yet commonly employed in biological simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns are presents in the work of [24], where the authors model the dynamics of the system using the S[B] paradigm [25] via delayed discrete automaton and persistent entropy. However, where they focus on the global dynamics of the system, we aim to capture the local interactions of each components.…”
Section: Introductionmentioning
confidence: 86%
“…An additional information returned by the computation of persistent homology is the list of the generators , which are the simplices involved in the holes. Experimentally, the generators play a crucial role for the description of the data under analysis [25, 26]. …”
Section: Main Textmentioning
confidence: 99%